AWK AND GNU OCTAVE PROGRAMMING LANGUAGES INTEGRATED WITH GENERIC MAPPING TOOLS FOR GEOMORPHOLOGICAL ANALYSIS - Polina LEMENKOVA (GeoScience Engineering, 2019)
The paper presents a sequential use of the AWK and GNU Octave programming languages integrated with Generic Mapping Tools (GMT) for geospatial data analysis. The geographic scope of the research is focused on the Kuril-Kamchatka Trench, north Pacific Ocean. Practical research aim is to analyse and compare bathymetry in the southern and northern part of the trench using digitized cross-section profiles. The initial mapping and geospatial analysis was performed in GMT scripting toolset. The GMT was used for cartographic mapping based on the raster ETOPO1 grid and automatic digitizing of the profiles crossing the trench perpendicularly. Besides visualized map, the processed geodata were received in a numerical form as a complex multi-field table for each segment. These tables were generated by the GMT in its native format and could not be directly processed by the MATLAB/Octave. Therefore, the tables were exported to AWK, a data-driven programming language and a powerful tool for data extraction. The table was then restructured, sorted and reshaped by the AWK script. Because the total amount of profiles overstepped 100 (62 and 52 for the northern and southern trench segments), only selected profiles were visualized. For this purpose, at the next step, the modified tables were converted to GNU Octave language for visualizing and plotting selected profiles. Finally, the geomorphology was analysed and two segments compared. The results show that the southern part has deeper bathymetric values, vary in geomorphic structure and has steeper gradient slopes comparing to the north, which is caused by the seismicity, volcanism, geologic and tectonic settings. Three full scripts of GMT, AWK and GNU Octave programming languages are presented for replicability in the Appendix.